Accounting Systems, Participation in Budgeting, and Performance Evaluation. - Penno, Mark (The Accounting Review, 1990)
Explores the use of accounting numbers in employee evaluation. Employee participation in accounting-based budgeting processes; Determination of employee participation; Links between accounting signals and performances expected to employees; Results of principal-agent analysis; Results of zero value to participation.